2018
DOI: 10.3389/fnint.2018.00033
|View full text |Cite
|
Sign up to set email alerts
|

Gut-Brain Psychology: Rethinking Psychology From the Microbiota–Gut–Brain Axis

Abstract: Mental disorders and neurological diseases are becoming a rapidly increasing medical burden. Although extensive studies have been conducted, the progress in developing effective therapies for these diseases has still been slow. The current dilemma reminds us that the human being is a superorganism. Only when we take the human self and its partner microbiota into consideration at the same time, can we better understand these diseases. Over the last few centuries, the partner microbiota has experienced tremendou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
173
0
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(186 citation statements)
references
References 376 publications
(626 reference statements)
1
173
0
12
Order By: Relevance
“…Earlier studies have reported the relationship between the brain and the GI system, the so-called gut-brain axis or brain-gut axis. It has been hypothesized that GI dysfunctions could reflect the disruptions of the microbiome-gut-brain axis, leading to serious GI inflammatory diseases (e.g., acute pancreatitis or inflammatory bowel disease), endothelial dysfunction, altered immune functioning and regulation of appetite control, neural inflammation, subsequent neurodegeneration, cognitive or psychoneurological disorders (e.g., depression, anxiety, autism, dementia), and disease progression of PD [8][9][10][11][12][13][14][15][16][17][18][19]. In addition to the use of peptides for the improvement of gastrointestinal or digestive dysfunctions [13,[20][21][22], and in order to improve GI function and the balance of microbiota, probiotics could be one of the powerful tools to be used for altering the PD-associated microbiota composition and mitigating the related inflammatory process [12,23].…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies have reported the relationship between the brain and the GI system, the so-called gut-brain axis or brain-gut axis. It has been hypothesized that GI dysfunctions could reflect the disruptions of the microbiome-gut-brain axis, leading to serious GI inflammatory diseases (e.g., acute pancreatitis or inflammatory bowel disease), endothelial dysfunction, altered immune functioning and regulation of appetite control, neural inflammation, subsequent neurodegeneration, cognitive or psychoneurological disorders (e.g., depression, anxiety, autism, dementia), and disease progression of PD [8][9][10][11][12][13][14][15][16][17][18][19]. In addition to the use of peptides for the improvement of gastrointestinal or digestive dysfunctions [13,[20][21][22], and in order to improve GI function and the balance of microbiota, probiotics could be one of the powerful tools to be used for altering the PD-associated microbiota composition and mitigating the related inflammatory process [12,23].…”
Section: Introductionmentioning
confidence: 99%
“…Reconstitution of Bifidobacterium infantis reversed the exaggerated HPA stress response in GF mice [115]. Since then, a series of observations, based on microbiota perturbation models (GF or antibiotic-treated animals), probiotic, or bioactive treatment models and fecal transplantation in animal models or human trials, indicated that gut microbiota are not only essential for maintaining normal neurophysiology and behaviors [116], but also influence the pathogenesis of various diseases, including neurologic disorders, gastrointestinal diseases, and metabolic disorders [117,118].…”
Section: Microbiota-gut-brain Axismentioning
confidence: 99%
“…There are various mechanisms of how intestinal microbiota can interact with the central nervous system and there is a broad outstanding literature covering microbiota-gut-brain axis interactions (32,211). In this article, we will approach this topic from the microbiota-gutimmune-glia (MGIG) axis perspective, and we will explore the role of microbiota in intestinal and BBB permeability in the regulation of microglial, oligodendrocyte and BBB maturation and functions (Figure 1).…”
Section: Intestinal Microbiota Modulate Glia Functionsmentioning
confidence: 99%